A systematic analysis of affinity tags in the haloarchaeal expression system, Haloferax volcanii for protein purification - Karan, Ram; Renn, Dominik; Allers, Thorsten; Rueping, Magnus (Frontiers in Microbiology, 2024)
Extremophilic proteins are valuable in various fields, but their expression can be challenging in traditional hosts like Escherichia coli due to misfolding and aggregation. Haloferax volcanii (H. volcanii), a halophilic expression system, offers a solution. This study examined cleavable and non-cleavable purification tags at both the N-and C-termini when fused with the superfolder green fluorescent protein (sfGFP) in H. volcanii. Our findings reveal that an N-terminal 8xHis-tag or Strep-tag®II significantly enhances protein production, purity, and yield in H. volcanii. Further experiments with mCherry and halophilic alcohol dehydrogenase (ADH) showed improved expression and purification yields when the 8xHis-tag or Strep-tag®II was positioned at the Cterminus for mCherry and at the N-terminus for ADH. Co-positioning 8xHis-tag and Twin-Strep-tag® at the N-terminus of sfGFP, mCherry, and ADH yielded significantly enhanced results. These findings highlight the importance of thoughtful purification tag design and selection in H. volcanii, providing valuable insights for improving protein production and purification with the potential to advance biotechnological applications.